THEORETICAL AND PRACTICAL FOUNDATIONS OF THE APPLICATION AND USE OF THE TELEMATICS SOLUTIONS FOR THE DEVELOPMENT OF THE NATIONAL ECONOMY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The authors’ research is interconnected with the socio-economic policy of the Republic of Belarus. Structural components and metrics of economic efficiency in the scientific work are studied based on government demand, which is reflected in the National Strategies for Sustainable Socio-Economic Development of the Republic of Belarus until 2020 and 2030. In addition, statistical data on the activities in economic sectors allows us to identify the most vulnerable areas of business, where telematics solutions can be used as drivers of growth and development. Considering that in the Republic of Belarus there are no fundamental studies on the application of business solutions based on the telematics tools for socio-economic development, the relevance, and reasonableness of the study is subsequently substantiated by economic results obtained from the analysis of the implementation of telematics solutions in foreign practice and in Belarusian business, that’s reflecting significant savings and cost reduction.